Novel Disease but responding to an Old Drug: Role of Prolonged Corticosteroid Use in Prevention and Treatment of Post-Covid Interstitial Lung Disease (PC-ILD) - Muhammad Waseem, Maryam Rafiq, Muhammad Waseem, Maryam Rafiq (Journal of Rawalpindi Medical College, 2022)
Coronavirus has affected more than 128 million humans worldwide with invasionsin 129 countries across the globe. About 5-10 percent of these patients have pulmonary involvement in the form of COVID Pneumonia leading to ARDS. Although there are no statistics at the moment, trends show that majority will get rid of acute COVID respiratory involvement without any long-term pulmonary complications however several patients will face COVID sequel in the form of post-COVID fibrosis or post-COVID interstitial lung disease. With more and more survivors of COVID-19, long-term pulmonary complications of this infection especially Post-COVID ILD are being recognized by treating physicians ashavinga great impact on patients’functionality and quality of life. Since there is no research-based internationally accepted strategy to prevent and treat Post-COVID ILD, a strategy based upon observations of treating pulmonologists was devised in the COVID management unit at Sahiwal Medical College Sahiwal to prevent and treat Post COVID interstitial lung disease.Keywords:Anti-fibrotic, Fibrosis, Post-COVID sequelae, Post-COVID fibrosis, Post-COVID ILD.